Long term effect of liquidity on stock market development - Balogun, Wakilat Olabisi; Dahalan, Jauhari; Hassan, Sallahuddin (2016)
The study investigates the long run relationship between stock market liquidity and development of stock market using panel dataset that spans 1990-2013 for seven selected Sub-Saharan African countries.It employs dynamic heterogeneous panel data analysis using the technique of Pooled Mean Group.Liquidity of the stock market is measured by both the stock value traded and turnover ratio.The result of PMG technique shows that there is a long run relationship between stock market liquidity and the development of stock market.It is thus recommended that the policy makers in these countries should design strategy to boost the liquidity of the stock market in order for the stock market to contribute to growth.